Optimization of Four-Wheeled Patrol Units by Samapta Units in Order to Prevent Curat Crimes in the Jurisdiction of Sukoharjo Police Station - Axel Huwae (Tanggon Kosala, 2023)
The author's final project raises the issue of "How to Optimize the Four-Wheeled Patrol Unit of the Samapta Unit in order to Prevent Theft with Aggravation in the Sukoharjo Police Jurisdiction". This Final Project aims to identify the method of implementation of the Sukoharjo Police Samapta Unit Four-Wheeled Patrol and the quality of human resources of the Sukoharjo Police Samapta Unit Four-Wheeled Patrol. This research uses a qualitative approach with the type of field research through limited observation, interviews, and document studies. The data sources used were also obtained from relevant articles, books, journals, and online media news. This research uses Management Theory, SWOT Theory and Competency Theory as well as four concepts relevant to the problem, namely the concept of patrol, the concept of kamtibmas, the concept of theft with weight and the concept of optimization in accordance with Perkabaharkam Number 1 of 2017 concerning Patrol. The results of the study found that the crime of theft with aggravation is the highest crime in the jurisdiction of Sukoharjo Police Station. The implementation of patrol activities carried out has problems in planning, organizing, implementing, and supervising. Based on the results of the study, the author suggests mapping vulnerable areas, coordination with police ranks, and direct supervision by the leadership of patrol implementation in accordance with Perkabaharkam Number 1 of 2017 concerning Patrols. To improve their human resources, it is necessary to increase the ability and insight of patrol members through discussion forums and training held by Sukoharjo Police Station so that the implementation of patrols can be optimal.